Corrosion behavior of Al/TiO2/Y2O3 hybrid nanocomposites manufactured using the vacuum-assisted stir casting route. Issue 5 (22nd June 2022) - Singh, Mandeep; Bhandari, Deepak; Goyal, Khushdeep
Abstract : Purpose: This study aims to examine the corrosion and flexural behaviour of advanced hybrid aluminium matrix nanocomposites (HAMNCs) made with a vacuum-assisted stir die casting (two-layer feeding) and reinforced with titanium oxide (TiO2 ) and yttrium oxide (Y2 O3 ) nanoparticles. The previous researchers have shown that TiO2 and Y2 O3 nanoparticles make aluminium composites much more resistant to corrosion and wear. Design/methodology/approach: Salt spray corrosion tests were done on the samples over time as well as the pre-and post-corrosion morphology of the test samples was also investigated. The density, porosity and energy dispersive X-ray of the fabricated samples were observed. Findings: It was observed that a lower corrosion rate of 0.127 mils/year and 0.573 mils/year was seen in the Al/5 Wt.%TiO2 /5 Wt.%Y2 O3 (HAMNC1) and Al/7.5 Wt.%TiO2 /2.5 Wt.%Y2 O3 (HAMNC3), respectively. It was evident from the results that the pores and densities of the samples varied with the filler concentrations and matrix filler wettability. HAMNC1 has the lowest values of density and porosity at 2.568 g/cm 3 and 9.91%, respectively. At the same time, a significant improvement in the flexural strength of 72 N/mm 2 was also seen in the HAMNC1 configuration. Practical implications: The proposed hybrid samples are well suited for aerospace and automobile structural components such as brake drums, discs, engine cylinders and fins. Originality/value: The mixed influence evaluation of TiO2 and Y2 O3 nanoparticles with pure Al on composite samples has not been studied. This research aims to examine the combined influence of nanoparticles on the corrosion aspects of two-step feeding vacuum stir casted products, as well as their morphology.